Maternal and Neonatal Outcomes of Placenta Previa with and without Coverage of a Uterine Scar: A Retrospective Cohort Study in a Tertiary Hospital - Rao J; Fan D; Zhou Z; Luo X; Ma H; Wan Y; Shen X; Lin D; Zhang H; Liu Y; Liu Z (Dove Medical Press, 2021)
Jiaming Rao,1 Dazhi Fan,1 Zixing Zhou,1 Xin Luo,1 Huiting Ma,1 Yingchun Wan,1 Xiuyin Shen,1 Dongxin Lin,1 Huishan Zhang,1 Yan Liu,2 Zhengping Liu1,2 1Foshan Fetal Medicine Institute, Affiliated Foshan Maternity & Child Healthcare Hospital, Southern Medical University (Foshan Maternity & Child Healthcare Hospital), Foshan, Guangdong, 528000, People's Republic of China; 2Department of Obstetrics, Affiliated Foshan Maternity & Child Healthcare Hospital, Southern Medical University (Foshan Maternity & Child Healthcare Hospital), Foshan, Guangdong, 528000, People's Republic of ChinaCorrespondence: Zhengping Liu; Yan LiuFoshan Fetal Medicine Institute and Department of Obstetrics, Affiliated Foshan Maternity & Child Healthcare Hospital, Southern Medical University (Foshan Maternity & Child Healthcare Hospital), Renminxi Road 11, Foshan, Guangdong, 528000, People's Republic of ChinaTel +86 757 82969878Fax +86 757 82969772Email liuzphlk81@outlook.com; liuyan20102011@163.comBackground: To compare the maternal and neonatal outcomes of placenta previa (PP) with and without coverage of a uterine scar in Foshan, China.Methods: A retrospective cohort study comparing all singleton pregnancies with PP was conducted at a tertiary, university-affiliated medical center from 1 January 2012 to 31 April 2017 in Foshan, China. Demographic, clinical and laboratory data were extracted from electronic medical records (EMRs). Maternal and neonatal outcomes of PP with and without coverage of a uterine scar were compared by statistical method.Results: There were 58,062 deliveries during the study period, of which 726 (1.25%) were complicated PP in singleton pregnancies and were further classified into two groups: the PP with coverage of a uterine scar group (PPCS, n=154) and the PP without coverage of a uterine scar group (Non-PPCS, n=572). Overall, premature birth (< 37 weeks, 67.5% vs 54.8%; P=0.019), cesarean section (100% vs 97.6%; P=0.050), intraoperative blood loss > 1000 mL (77.9% vs 16.0%; P< 0.001) or > 3000mL (29.9% vs 3.0%; P< 0.001), bleeding within 2-24 hours after delivery (168.2± 370.1 ml vs 49.9± 58.4 ml; P< 0.001), postpartum hemorrhage (48.7% vs 15.7%; P< 0.001), transfusion (34.6% vs 16.1%; P< 0.001), hemorrhage shock (7.8% vs 1.9%; P< 0.001), hysterectomy (2.6% vs 0.5%; P=0.019), fetal distress (35.7% vs 12.1%; P< 0.001) and APGAR score at 1 min (15.2% vs 7.1%; P=0.002) had a significant difference between PPCS group and Non-PPCS group. After grouping by whether complicated with placenta accreta spectrum disorders (PASD), we found that PPCS was significant associated with more intraoperative blood loss > 1000mL, intraoperative blood loss > 3000mL, bleeding within 2- 24 hours after delivery and fetal distress than the Non-PPCS group.Conclusion: The PPCS group had poorer maternal and neonatal outcomes than the Non-PPCS group after grouping by whether pregnancies complicated with PASD or with different placental positions.Keywords: placenta previa, placenta accreta spectrum disorders, pregnancy outcomes, uterine scar, hysterectomy, cesarean section